Effect of stored some legumes seeds infected with Callosobruchus maculatus (Fab.) (Coleoptera:Bruchidae) cowpea weevil under different temperature degrees in the level of contamination with aerobic bacteria - علي, صادق ثاجب (University of Thi-Qar Journal of Science, 2014)
Present study was carried out to evaute the effection of the different temperature degrees (20C,25C, 30C), in thelevel of contamination of attacked and non – attacked legume seed with Cowpea weevil with aerobic bacteria andstored for two generations. Results showed that attacked and non attacked legumes are contaminated with thebacterial species Staphylococcus aureus, S. epdermidis and Pseudomonas aeurginosa in three temperature degrees.Differed contamination level quantitative types of bacteria above depending on temperature was the highest rate forthe preparation of the bacteria when the temperature is 30C in cowpea seeds reaching 782875 × 103 cells / g and thelowest rate was in the seeds of chickpeas when degree heat 25 C and of 515 × 103 cells / g . For dates sampling has emerged that two weeks after the appearance of the first generation in temperature 30 C distinct from the rest of theappointments reaching 7705666 × 103 colony / gm while the 8845 and 221273 × 103 cells / g after the appearance ofmembers of the second generation of degree heat 20 C and 25 C on respectively.